Evaluating the software development processes at Experian: What would it take Experian to achieve CMMI maturity level 3? - Sankhe, Tejas (2009)
In today’s high-technology environment, most organisations build complex products and services. Organisations however rarely build all the components of their product/service. Instead, they produce bits and pieces of the same and finally integrate them into a single product/service. Such complex development and maintenance processes require good management and control.